2016
DOI: 10.1128/iai.00486-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Cell-Mediated Response in Dogs Naturally Infected by Leishmania infantum

Abstract: A genome-wide association study (GWAS) could unravel the complexity of the cell-mediated immunity (CMI) to canine leishmaniasis (CanL). Therefore, we scanned 110,165 single-nucleotide polymorphisms (SNPs), aiming to identify chromosomal regions associated with the leishmanin skin test (LST), lymphocyte proliferation assay (LPA), and cytokine responses to further understand the role played by CMI in the outcome of natural Leishmania infantum infection in 189 dogs. Based on LST and LPA, four CMI profiles were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Hosts who activate the humoral immune response or Th2 pathway develop the disease with greater prevalence and severity since the antibodies are ineffective and stimulation by cytokines is based on the production of IL-10. This situation favors the development of the parasite along with the arginase enzyme and synthesis of polyamides [37]. Studies in vitro have demonstrated that blocking the activity of receptor IL-10 may be a new effective treatment [38,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosts who activate the humoral immune response or Th2 pathway develop the disease with greater prevalence and severity since the antibodies are ineffective and stimulation by cytokines is based on the production of IL-10. This situation favors the development of the parasite along with the arginase enzyme and synthesis of polyamides [37]. Studies in vitro have demonstrated that blocking the activity of receptor IL-10 may be a new effective treatment [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different canine breeds present different prevalence rates [ 40 , 41 ]. Genes related to the activation of Th1 pathways include IL12RB1, JAK3 , CCRL2 , CCR2 , CCR3 , and CXCR6 , whereas COMMD5 and SHARPIN are associated with the activation of Th2 pathways [ 37 ]. Other genes, such as Slc11c11 or Major Histocompatibility Complex I gene ( MHCI ), also affect the susceptibility or resistance to L. infantum infection [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lama2 -deficient mouse model shows elevated expression of proinflammatory cytokines, concretely, TNF-α and IL1β [ 53 ], and Li et al [ 57 ] demonstrated that LAMA2 is a coreceptor to activate T cells upon infection by S. aureus [ 54 ]. Thirteen intronic polymorphisms have been found in LTBP1 gene, a known gene involved in T regulatory lymphocyte differentiation [ 14 ]. In fact, Batista et al [ 14 ] performed a genome-wide association study of cell-mediate response in dogs infected by L. infantum , and their results showed several genetic markers, which explain the phenotypic variance in cytokines expression [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The allelic status of previously published polymorphisms and genomic regions described as related to the immune response to L. infantum infection in dogs [ 12 , 14 19 ] were interrogated in the analyzed samples.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts involving EMMAX include discovery of susceptibility loci for CanL [ 19 ], loci associated with canine cell-mediated response to L . infantum [ 22 ] and susceptibility human VL loci replicated in two independent samples [ 23 ]. In fact, the combination of an adjusted linear regression model with EMMAX restricted genomic inflation to acceptable levels even in a sub-structured multi-racial panel as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%